Effect of repeated intratracheal instillation of incense smoke condensate in mice - In-Hyeon Kim; Je-Hein Kim; Se-Woong Park; Han Na Suh; Su-Jin Lim; Min-Sung Kang; Hyeon-Young Kim; Dong Im Kim; Moonjung Hyun; Sung-Hwan Kim (PLoS ONE, 2025)
Incense smoke condensate (ISC) can have harmful mutagenic and genotoxic effects. Epidemiological and experimental studies have reported the negative effects of incense use on humans. We investigated the toxicological effects of the incense smoke condensate ISC in a 2-week repeated intratracheal instillation model in mice. Twenty-five male mice were divided into four treatment groups and one control group (n = 5 per group). The treatment groups received daily intratracheal instillations of ISC at doses of 2.5, 5, 10, and 20 mg/kg/day, and the control group received a vehicle control for the duration of the study. Mortality and body weight were recorded during the study period. At the end of the study, all mice were sacrificed and terminal body weight, organ weight, gross findings, total and differential cell counts in the bronchoalveolar lavage fluid (BALF), and histopathological findings were obtained. Lung inflammatory markers were measured using quantitative real-time polymerase chain reaction. The results showed that ISC exposure led to dose-dependent increases in both absolute and relative left lung weights, as well as in the number of total cells, macrophages, and neutrophils in BALF. Furthermore, the ISC significantly elevated the mRNA expression levels of inflammatory markers such as IL-1β, IL-6, TNF-α, and MMP-12 in the lung tissues in a dose-dependent manner. Histopathological analysis revealed significant changes in the lungs, including epithelial hyperplasia, inflammatory cell infiltration, and macrophage aggregation. These findings indicate that ISC induces lung inflammation. The no-observed-adverse-effect level of ISC was determined to be less than 2.5 mg/kg/day in this mouse model.